Unqualified audit report and non-compliance with IFRS: Interview evidence - Nazli, Ismail@Nawang; Mazni, Abdullah; Noor Sharoja, Sapiei (2017)
This study aims to explore the reasons why an unqualified audit report was issued despite non-compliance with the International Financial Reporting Standards (IFRS) disclosure requirements. To achieve this objective, a semi-structured interview was used to gather opinions of auditors. Our findings suggest that materiality and true and fair view could be the reasons for issuing a clean audit report despite significant non-compliance with accounting standards. The findings of this study might assist regulators, standard setters and professional accounting bodies in monitoring and safeguarding the quality of financial reporting.